Coexpression of SOX10/CD271 (p75NTR) and β-Galactosidase in Large to Giant Congenital Melanocytic Nevi of Pediatric Patients - Marjam J. Barysch; Mitchell P. Levesque; Phil Cheng; Maria B. Karpova; Daniela Mihic-Probst; Gianluca Civenni; Olga Shakhova; Lukas Sommer; Thomas Biedermann; Clemens Schiestl; Reinhard Dummer (MDPI AG, 2014)
Background: Congenital melanocytic nevi (CMNs) are melanocytic neoplasms that can transform into melanoma. However, this development is impeded in the majority of cases and mostly affects patients with large or giant CMNs. Methods: To elucidate mechanisms that keep CMNs from malignant transformation, CMN tissue biopsies were investigated for p-ERK and senescence markers by immunohistochemistry and for SOX10/CD271 (p75NTR) by immunofluorescence. CMN cells were cultivated, and MTT assays were performed for evaluating cell viability. Mutation status for NRAS and BRAF was performed by real-time PCR. Results: 13 CMNs (from patients aged 0.5-11.8 years, mean: 2.7) showed immunoreactivity for SOX10/CD271 (p75NTR) in 34.2%. p-ERK was immunoreactive in 80% (4/5); β-galactosidase was significantly stronger expressed in CMNs compared to melanocytic nevi of patients over 70 years (p = 0.0085). The 5 CMN cultures were immunoreactive for SOX10/CD271 (p75NTR) in 36.7%. By silencing SOX10 by siRNA in 2 CMN cell cultures, cell viability decreased significantly. NRASQ61K mutation was found in 91.7% (11/12) and BRAFV600E in 6.3% of all analyzable CMNs (1/16). Conclusions: Oncogene-induced senescence might prevent malignant transformation through activation of the mitogen-activated protein kinase pathway. SOX10 is necessary for the viability of human CMN cell cultures and may be responsible for clinical changes during aging. © 2014 S. Karger AG, Basel